2021
DOI: 10.1002/cpt.2383
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interactions Involving 17α‐Ethinylestradiol: Considerations Beyond Cytochrome P450 3A Induction and Inhibition

Abstract: It is widely acknowledged that drug‐drug interactions (DDIs) involving estrogen (17α‐ethinylestradiol (EE))‐containing oral contraceptives (OCs) are important. Consequently, sponsors of new molecular entities (NMEs) often conduct clinical studies with priority given to OCs as victims of cytochrome P450 (CYP) 3A (CYP3A) induction and inhibition. Such scenarios are reflected in the US Food and Drug Administration‐issued guidance documentation related to OC DDI studies. Although CYP3A is important, OCs such as EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…Despite the recognition that sulfation plays an important role in EE metabolism, the effect of an investigational drug on sulfotransferases (e.g., SULT1E1) is not routinely assessed in in vitro experiments during drug development. A recently published review article also underscores the importance of including SULT1E1 (and UGT1A1) during drug development when evaluating the DDI potential with EE-containing COCs (Rodrigues, 2022). As this is a recently recognized interaction, clinical studies evaluating the impact of SULT inhibition on EE clearance are limited.…”
Section: Eementioning
confidence: 99%
“…Despite the recognition that sulfation plays an important role in EE metabolism, the effect of an investigational drug on sulfotransferases (e.g., SULT1E1) is not routinely assessed in in vitro experiments during drug development. A recently published review article also underscores the importance of including SULT1E1 (and UGT1A1) during drug development when evaluating the DDI potential with EE-containing COCs (Rodrigues, 2022). As this is a recently recognized interaction, clinical studies evaluating the impact of SULT inhibition on EE clearance are limited.…”
Section: Eementioning
confidence: 99%
“…In this regard, EE presents as a DDI victim because it is a sulfotransferase 1E1 (SULT1E1), UDP‐glucuronosyltransferase 1A1 (UGT1A1), and cytochrome P450 3A4 (CYP3A4) substrate. This means that one needs to consider all 3 enzymes when attempting to understand EE DDI 1 . As an example, Helmer et al reported that ziritaxestat (autotaxin inhibitor) significantly impacts the pharmacokinetic (PK) profile of EE 2 .…”
Section: Parameter/information Etoricoxib Ziritaxestat Referencementioning
confidence: 99%
“…It was concluded that the DDI with EE involved SULT1E1 after showing that it was inhibited by ziritaxestat in vitro (half‐maximal inhibitory concentration, IC 50 < 0.8 μ M) (Table 1). Such an approach is logical, because SULT1E1 is expressed in the intestine and liver and plays a major role in EE first‐pass metabolism 1,4 . Of note, ziritaxestat is not the first example of an EE DDI involving SULT1E1 inhibition.…”
Section: Parameter/information Etoricoxib Ziritaxestat Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Like natural hormones, synthetic estrogens display estrogenic activity by binding to estrogen receptors a (ESR1) and b (ESR2). They might be more resistant to metabolism and inactivation than the natural hormone 17β-estradiol (E2) (E2) [ 4 , 6 ]. These molecules can cross the placental barrier [ 7 ] and are metabolized in the liver by cytochrome P450-like enzymes, most often producing inactive metabolites [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%